Competitive Ability of Maize Pollen Grains Requires Paralogous Serine Threonine Protein Kinases STK1 and STK2. Issue 4 (6th October 2017) - Huang, Jun T; Wang, Qinghua; Park, Wonkeun; Feng, Yaping; Kumar, Dibyendu; Meeley, Robert; Dooner, Hugo K
Abstract: serine threonine kinase1 ( stk1 ) and serine threonine kinase2 ( stk2 ) are closely related maize paralogous genes predicted to encode serine/threonine protein kinases. Pollen mutated in stk1 or stk2 competes poorly with normal pollen, pointing to a defect in pollen tube germination or growth. Both genes are expressed in pollen, but not in most other tissues. In germination media, STK1 and STK2 fluorescent fusion proteins localize to the plasma membrane of the vegetative cell. RNA-seq experiments identified 534 differentially expressed genes in stk1 mutant pollen relative to wild type. Gene ontology (GO) molecular functional analysis uncovered several differentially expressed genes with putative ribosome initiation and elongation functions, suggesting that stk1 might affect ribosome function. Of the two paralogs, stk1 may play a more important role in pollen development than stk2, as stk2 mutations have a smaller pollen transmission effect. However, stk2 does act as an enhancer of stk1 because the double mutant combination is only infrequently pollen-transmitted in double heterozygotes. We conclude that the stk paralogs play an essential role in pollen development.